Mesenchymal Stromal/Stem Cells and Their Extracellular Vesicles Application in Acute and Chronic Inflammatory Liver Diseases: Emphasizing on the Anti-Fibrotic and Immunomodulatory Mechanisms - Hazrati, Ali; Malekpour, Kosar; Soudi, Sara; Hashemi, Seyed Mahmoud (Frontiers in Immunology, 2022)
Various factors, including viral and bacterial infections, autoimmune responses, diabetes, drugs, alcohol abuse, and fat deposition, can damage liver tissue and impair its function. These factors affect the liver tissue and lead to acute and chronic liver damage, and if left untreated, can eventually lead to cirrhosis, fibrosis, and liver carcinoma. The main treatment for these disorders is liver transplantation. Still, given the few tissue donors, problems with tissue rejection, immunosuppression caused by medications taken while receiving tissue, and the high cost of transplantation, liver transplantation have been limited. Therefore, finding alternative treatments that do not have the mentioned problems is significant. Cell therapy is one of the treatments that has received a lot of attention today. Hepatocytes and mesenchymal stromal/stem cells (MSCs) are used in many patients to treat liver-related diseases. In the meantime, the use of mesenchymal stem cells has been studied more than other cells due to their favourable characteristics and has reduced the need for liver transplantation. These cells increase the regeneration and repair of liver tissue through various mechanisms, including migration to the site of liver injury, differentiation into liver cells, production of extracellular vesicles (EVs), secretion of various growth factors, and regulation of the immune system. Notably, cell therapy is not entirely excellent and has problems such as cell rejection, undesirable differentiation, accumulation in unwanted locations, and potential tumorigenesis. Therefore, the application of MSCs derived EVs, including exosomes, can help treat liver disease and prevent its progression. Exosomes can prevent apoptosis and induce proliferation by transferring different cargos to the target cell. In addition, these vesicles have been shown to transport hepatocyte growth factor (HGF) and can promote the hepatocytes'(one of the most important cells in the liver parenchyma) growths.